Rise of Post Modernism and Revitalization of Cultural Heritage in Taxila: An Insight - Hafeez, Swera; Chaudhry, Abid Ghafoor (Annals of Human and Social Sciences, 2023)
This study delves into the interconnected phenomena of postmodernism’s emergence and the subsequent revitalization of cultural heritage. Through examining historical, social, and cultural factors, the study establishes a connection between the rise of postmodernism and the revitalization of cultural heritage. The contemporary era of postmodernism and globalization is causing the homogenization of different cultures, ethnicities, languages, and traditions. The emergence of an identity crisis is another dilemma. This evolution is a complex and simultaneous paradigm; hence, it is necessary to retain the distinguished and unique recognition by being modern and sticking to the actual roots simultaneously. The study incorporates a multidisciplinary approach, implementing insights from cultural studies, archaeology, sociology, and religious studies. Exploratory research methodology with in-depth interviews and focused group discussions has been employed with a randomly selected sample of 12 respondents using interview guides as a tool for qualitative research. The significant findings suggest that postmodernism has played a pivotal role in the revitalization of cultural heritage by encouraging critical engagement with the past, fostering a sense of belonging, and promoting cultural exchange. It is recommended to take actions and formulate policy to enhance collaboration with other stakeholders, such as local authorities, conservation organizations, and community groups, to ensure a comprehensive approach to conservation.